Impact Of Service Quality On Corporate Image Among PHEIs In Malaysia - Ying Hoe, Dennis Choo (2011)
This work examined the relationship between service quality dimensions and corporate image of private higher education institutions (PHEIs) and reviewed the role of gender as a moderating variable and performance service quality as a mediating variable.